Establishing Ethical Norms: Dignified Justice Theory Perspectives on Ethics and Legal Relations: Mendudukkan Norma Etika: Perspektif Teori Keadilan Bermartabat terhadap Relasi Etika dan Hukum - Disantara, Fradhana Putra; Anggono, Bayu Dwi; Efendi, Aan (Universitas Muhammadiyah Sidoarjo, 2022)
The relationship between ethical norms and legal norms is different for experts, especially concerning their position. Moreover, legal norms seem to be superior to ethical norms. This study aims to analyze the position of ethical norms and legal norms. The dignified justice theory was chosen because it seeks to orient the divine and human aspects, which can only be fulfilled if ethical and legal norms synergize. This research is juridical-normative research. The juridical-normative research was chosen because it confirms the existence of ethical norms and legal norms as part of the system of norms prevailing in society. The study's results confirm that, in practice, legal court decisions are often considered higher and more authoritative than ethical court decisions. This has implications for the position of ethical norms that are considered inferior to legal norms. Furthermore, the theory of dignified justice seeks to see the relationship between ethical norms and legal norms as different norms, but in its implementation in society, the two norms must synergize and complement each other.